Incidence of invasive Group B Streptococcus (iGBS) infections and the factors associated with iGBS mortality in adults during 2013–2017: a retrospective study at Thailand’s largest national tertiary referral center - Pakpoom Phoompoung (2022)
Objectives: To determine the incidence of invasive Group B streptococcal (iGBS) diseases and the factors significantly associated with iGBS mortality in adult patients. Material and methods: This retrospective study included adults with a positive culture for GBS isolated from a sterile site at Siriraj Hospital–Thailand’s largest tertiary care hospital–during January 2013 to December 2017. Results: Of the 224 included patients, 75.9% had bacteraemia. The median age of patients was 63 years (interquartile range [IQR]: 53–73) and 52.7% were female. Among the 80% of all patients with comorbid diseases, diabetes mellitus (38.8%), cancer (18.8%), and heart disease (12.5%) were the most common. Skin and soft tissue infection (30.8%), septic arthritis (21.4%), primary bacteraemia (21.0%), and meningitis (7.1%) were the most common manifestations of iGBS diseases. The overall 30-day mortality was 11%. Patients that died were older and had more chronic kidney disease, bacteraemia, urinary tract infection, pneumonia, and iGBS-related morbidities than survivors. Pneumonia was the only factor independently associated with 30-day mortality with an adjusted odds ratio of 24.96 (95% confidence interval [CI]: 5.95–104.75). Conclusions: Invasive GBS is not uncommon in non-pregnant adults, particularly among older adults and those with diabetes. Concomitant bacteraemia was frequently observed in iGBS patients. The overall mortality was low, but significant morbidities were observed.KEY MESSAGES In our study, iGBS was not uncommon among older adults and those with diabetes. Two-thirds of patients with iGBS had bacteraemia, and the overall 30-day mortality was 11%.